Nephrological and Oncological Outcomes of Nephron Sparing Surgery for Renal Tumors in Solitary Functioning Kidney - Liaqat Ali, Muhammad Shah, Mohammad Shahzad, Faiza Hayat, Mohammad Hanif, Nasir Orakzai, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Renal cell carcinoma accounts for 90% of all cases of kidney cancer. The major treatment option available is radical Nephrectomy with 93% survival rate. In the literature, partial nephrectomy, nephron sparing surgery and cryoablation all have been mentioned with similar effects. The unavailability of cryoablation in a third-world country like Pakistan has forced urologists to undergo Nephron Sparing Surgery. Objective: To assess the nephrological and oncological outcomes of nephron sparing procedures in individuals with single functioning kidney and renal tumor. Methodology: This retrospective study was piloted at the Department of Urology & Transplantation, Institute of Kidney Diseases Peshawar for duration of eight years from 2012 to 2020. There were 45 patients enrolled in our study. All the required information was collected on a predesigned Performa. Data analysis was carried out by using IBM SPSS version 24. Results: In the current study, 45 patients with a solitary functioning kidney and renal tumor were selected. There were 39 (86.67%) males and 6 (13.33%) female patients in our study. The serum urea and creatinine levels in 44 (97.78%) patients were normal, while one patient had a preoperative creatinine level of 3.1mg/dl. Oncocytoma was the only tumor in which creatinine levels were improved after surgery. Only one patient with T3 disease developed liver metastasis and died after 38 months of surgery with normal urea and creatinine levels. There had been no recurrence, progression, or metastasis in 44 patients (97% percent). Conclusions: Nephron sparing surgery is equally effective in terms of Nephrological and Oncological outcomes in patients having solid renal tumors in solitary functioning kidneys. Keywords: Nephrological, Oncological, Outcome , Renal tumors, Clear cell carcinoma